IMPACT OF A QUALITY IMPROVEMENT INITIATIVE ON UNPLANNED EXTUBATION (UE) RATE IN THE NEONATAL INTENSIVE CARE UNIT (NICU). (18th May 2018) - Hewitt, Mark; Sproul, Erin; Hudson, Jo-Anna; Emberley, Julie
Abstract: BACKGROUND: Unplanned extubations (UEs) refer to any removal of an endotracheal tube not directly ordered or intended by the medical team. It is the fourth most common adverse event in the neonatal intensive care unit (NICU) and can lead to significant morbidity in this vulnerable population. A large proportion of UEs in the NICU are deemed preventable and UE rates are increasingly being recognized as an important quality of care metric. OBJECTIVES: To examine the effectiveness of an education-based quality improvement initiative to decrease UE rate in a level II/III NICU with a high rate of UEs DESIGN/METHODS: Pre-intervention UE rate was determined by retrospective chart review for all intubated neonates admitted to a 25 bed level II/III NICU from January 2013 until December 2013. UEs were recorded along with demographic information including reason for extubation. UE rate was calculated by number of UEs/100 ventilator days and the data was analyzed to determine any significantly associated risk factors. The UE quality improvement initiative included: multi-disciplinary NICU staff education sessions, placement of educational posters in the NICU and identification of high risk neonates as defined by the pre-intervention study. High risk neonates were given additional signage to alert care providers. Standardized documentation was implemented to track and record UEs prospectively. Six months post-implementation, all UE events were reviewed from December 2015 until May 2016 and the post-intervention UE rate was calculated. RESULTS: The UE rate was 3.28 UEs/100 ventilator days in the pre-intervention cohort with neonatal movement and adhesive failure accounting for over 50% of the documented UEs. Regression analysis revealed total ventilation time to be the only significant (p<0.05) risk factor for an UE. In the post-intervention cohort the UE rate was 1.45 UEs/100 ventilator days, a 56% decrease from the pre-intervention rate. Rates of re-intubation following an UE were 78.3% and 50% for the pre- and post-implementation cohorts respectively. CONCLUSION: Reduction in UE rate from 3.28 to 1.45 was achieved with an education-based multi-disciplinary quality improvement initiative. Rates of re-intubation following an UE were similar between cohorts. Further study is necessary to evaluate whether the effectiveness of this intervention will persist over time and whether results are generalizable to other NICUs.